The importance of being vigilant: has ECB communication influenced Euro area inflation expectations? - David-Jan Jansen; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2007)
Using daily data on inflation-indexed bonds, we find evidence of a negative relationship between ECB communication regarding risks to price stability - measured on the basis of the frequency and strength of the keyword vigilance' - and changes in euro area break-even inflation. However, this result is only found for the second half of 2005. At that time, the start of a tightening of ECB monetary policy was increasingly likely. This suggests that communication should be closely in line with policy actions before it can be effective. Still, we also find that the economic significance of this type of communication has been small.
Keywords: E52; E58; 330; central bank communication; ECB; inflation expectations; Staatliche Information; Zentralbank; Inflationserwartung; Schätzung; EU-Staaten